Aspek Pemasaran - Adhari, Ayuna; Deffa Ray, Muhammad; Mahvi, Muhammad Rizky (Teewan Journal Solutions, 2025)
Marketing is one of the important aspects in the success and growth of a company. To achieve the desired marketing goals, companies must implement effective marketing concepts, including marketing mix, customer satisfaction, marketing plan preparation, and marketing program effectiveness audit. This study aims to analyze the application of these concepts in the company, as well as measure their effectiveness in achieving the marketing goals that have been set. Using a qualitative approach with a case study design at ABC company which operates in the food and beverage product sector. The results of the study indicate that the implementation of the right marketing mix can increase customer satisfaction, while the preparation of a mature marketing plan greatly influences the effectiveness of the marketing program. In addition, marketing effectiveness audits allow companies to evaluate marketing performance and make necessary improvements. This study provides deeper insight into how companies can optimize marketing strategies to achieve better success.